Strategic delegation and international permit markets: Why linking may fail - Wolfgang Habla; Ralph Winkler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We analyse a principal-agent relationship in the context of international climate policy. Principals in two countries first decide whether to merge domestic emission permit markets to an international market, then delegate the domestic permit supply to an agent. We find that principals select agents caring less for environmental damages than they do themselves in case of an international market regime, while they opt for self-representation in case of domestic markets. This strategic delegation incentive renders the linking of permit markets less attractive and constitutes a novel explanation for the reluctance to establish non-cooperative international permit markets.
urn:nbn:de:bsz:180-madoc-433663
Keywords: D72; H23; H41; Q54; Q58; 330; non-cooperative climate policy; political economy; emissions trading; linking of permit markets; strategic delegation